2021
DOI: 10.1007/s11606-021-06786-6
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Microaggressions with Depressive Symptoms and Institutional Satisfaction Among a National Cohort of Medical Students

Abstract: BACKGROUND: Despite substantial research on medical student mistreatment, there is scant quantitative data on microaggressions in US medical education. OBJECTIVE: To assess US medical students' experiences of microaggressions and how these experiences influenced students' mental health and medical school satisfaction. DESIGN AND PARTICIPANTS: We conducted a crosssectional, online survey of US medical students' experiences of microaggressions. MAIN MEASURES: The primary outcome was a positive depression screen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
78
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 67 publications
(83 citation statements)
references
References 49 publications
5
78
0
Order By: Relevance
“…Few studies have assessed discrimination as a risk factor for adverse mental health outcomes among HCWs, and most focus on physicians and physicians-in-training. Studies have identified that racial and gender discrimination were associated with increased risk of burnout among physicians [33] and depression among medical students [34]. Discrimination was also associated with anxiety and depression in a study including nurses in London [35].…”
Section: Discussionmentioning
confidence: 97%
“…Few studies have assessed discrimination as a risk factor for adverse mental health outcomes among HCWs, and most focus on physicians and physicians-in-training. Studies have identified that racial and gender discrimination were associated with increased risk of burnout among physicians [33] and depression among medical students [34]. Discrimination was also associated with anxiety and depression in a study including nurses in London [35].…”
Section: Discussionmentioning
confidence: 97%
“…The fully adjusted model included participant demographics, experiences, and medical student characteristics variables (sex, age, marital status, student loans, discrimination events, and school type) that could or have been shown to contribute to burnout symptoms. 3,13,34,35 Odds ratios (ORs) and 95% CIs were calculated to quantify the strength of observed associations. All statistics were performed using R version 3.6.3 (R Foundation).…”
Section: Discussionmentioning
confidence: 99%
“…Social stress theory as a framework explains that the prejudices (eg, sexism, racism, homophobia) present in the social environment act as sources of stress that might have considerable, negative impact to the mental and physical wellbeing of members of marginalized groups 12. Prior research has also found that microaggressions have been associated with positive depression screening among US medical students 13. Among physicians, workplace discrimination based on race or ethnicity has been associated with lower career satisfaction and increased physician turnover 14.…”
Section: Introductionmentioning
confidence: 99%